Kekerasan Verbal Pasangan Suami Istri di Daerah Ujungbatu Kabupaten Rokan Hulu - Asih Ria Ningsih; Rita Arianti; Misra Nofrita; Muslim Muslim (Jurnal Bahasa dan Sastra, 2021)
Verbal violence in husband-wife communication relationship is a phenomenon that is almost often found in every household with different intensity and levels. The purpose of this study was to describe the acts of verbal violence between husband and wife in Ujungbatu, Rokan Hulu district. The formulation of the problems studied in these study are: 1) knowing the form of verbal violence between husband and wife in the Ujungbatu area, 2) knowing the faktors that cause verbal violence between husband and wife couples in Ujungbatu area. This research is a qualitative descriptive research. The source of the data was obtained through wives who experienced acts of verbal violence. Data collection methods used are observation, interviews, recording, and notes. The results of this study indicate that verbal violence by husband and wife consists of: 1. the forms of verbal violence experienced by married couples are 25 utterances. These forms can be categorized into 4 types, namely direct speech acts of violence consisting of 15 utterances, indirect violence of 4 utterances, speech acts of repressive violence consisting of 4 utterances, and speech acts of alienative verbal violence consisting of 2 utterances. 2. Factors that cause acts of verbal violence include what factors you want to convey, state factors, mood factors and environmental factors.